D O C U M E N T 4 1 8 C A L C U L A T I O N S I N D I A R Y 6 8 1 [p. 46v] 1 2 --RαβRμνRμν - σ 1 2 --Rατδσ - β RμνRμν τ 0 Rαβ σ Rατ( Γστ β Γτσ β ) += R τ ατ δσ β Rατδσ β ∂lg D ∂xτ ---------------- Γντ ν Rαβ ∂lg D ∂xσ ---------------- - Γστ τ + 1 2 --RμνRμν - τ Γντ ν Γτν ν ( ) + δAμ Γαβ μ Aαdxβ –= δBμ Γ'μβ α Bαdxβ += = Γμ αβ Γ'αβ)AαBμdxβμ + ( 1 2 --RμνRμν - σ Γνσ ν Γσν ν ( ) + 0 Rαβ σ = τ δσ β –Rατ Rατ( Γστ β Γτσ β ) RατSσ β Γντ ν Γτν ν ( ) Rαβ( Γνσ ν Γσν ν ) + + + 1 2 --Rβα - σ + 0 1 2 --Rαβ - σ 1 2 --Rατ - τ δσ β 1 2 --Rβτ - τ δσ α 1 2 --RαβRμν - μ Rμν σ 1 4 --Rατδσ - β 1 4 --Rβτδσ - αEτ = 1 ) symmetrisches R Rαβ: 0 1 2 --Dσ - 1 2 --Dσ - 2Eσ 1 4 --Eσ - 1 4 --Eσ - 3 2 --Eσ - σ Dσ[40] + + = = 3E 2D + 0 = 2E D + 0 = E D 0 Rαβ σ 0 = = = 2 ) Voraussetzung der Symmetrie aufgehoben RαβRα'β δα'α = hebenso mit erstem Ind. Rαβ αβ Sαβ Aαβ += Rβα Sαβ Aαβ Rαβ 2Aαβ = = Rαβ Rα'βRαβ' Rα'β' = Sαβ s 1 2 --Sατ - τ δσ β 1 2 --Sβτ - τ δσα 0 Sαβ σ 1 2 --Dαδσ - β 1 2 --Dβδσ - α 1 2 --SαβEσ - 1 4 --Sατδσ - β 1 4 --Sβτδσ - αEτ = 1 2 --AαβEσ - 1 4 --Aατδσ - β 1 4 --Aβτδσ - αEτ Sαβ 0 1 2 -- - Es 1 2 --RαβSαβ - –= δβ σ: 0 2Dα 1 2 --Dα - 1 2 --Eα - 2Eα 1 2 --Eσ - 3Eσ 3 2 --D2 - + = = [39] [42] [41]
Previous Page Next Page